Lycopodiella inundata (Lycopodiaceae) en el Parque Natural de Peñalara (Sierra de Guadarrama, Madrid). Síntesis corológica y conservación. - Baonza, J.; Montouto, O. (Botanica Complutensis, 2001)
BAONZA, J. & MONTOUTO O. 2001. Lycopodiella inundata (L.) J. Holub (Lycopodiaceae) in the Peñalara Natural Park (Guadarrama range, Madrid). Chorological synthesis and conservation. Bot. Complutensis 25: 299-304. The second provincial record from Madrid of the pteridophyte Lycopodiella inundata (L.) J. Holub (Lycopodiaceae) is presented. It was located in the Peñalara Natural Park (Rascafría, Guadarrama range). Ecological and conservation local data are also included. In adittion peninsular distribution is studied.
Keywords: Lycopodiella inundata; Peñalara; Madrid; ecology; chorology; conservation